PEMANFAATAN SERAT PELEPAH KELAPA SAWIT SEBAGAI BAHAN PEMBUATAN KAMPAS REM SEPEDA MOTOR - Guntoro Guntoro; Ingrid Ovie Yosephine; Simon Simanjuntak (The University of Lampung, 2021)
Brake pads are generally made of asbestos, which is less environmentally friendly and widely available in nature, therefore motorcycle brake pads are made that utilize palm frond fibers filled with alumina powder and bonded to a polyurethane matrix. This research was conducted at the Laboratory of Material Testing of Industrial Chemical Technology Polytechnic (PTKI) Medan. Research was carried out from February-July 2020, using two test, namely the Rockwell Hardness level test and the Pin On Disk Friction Coefficient test. The result showed that oil palm frond fibers can be made into motorcycle brake pads with the addition of alumina powder according to the predetermined composition. After going through the test, the Rockwell hardness level was obtained in A2 treatment (6% Alumina) with the highest and best hardness level, namely 52.75 Kg. And after testing the friction coefficient of the Pin On Disk type, brake pads from palm frounds with the addition of alumina powder composition which have the lowest coefficient value of the best are obtained in treatment A2 (6% Alumina) with a value of 0.000765 N/mm2. Keywords : biocomposite, brake shoes, palm fround fibers, alumina powder